Changes in levels of C-reactive protein in open appendectomy compared to laparoscopic appendectomy - Askarpour, Shahnam; Asgari, Mehdi; Hashemi, Solmaz; Javaherizadeh, Hazhir (Gastroenterology Review/Przegląd Gastroenterologiczny, 2012)
Aim : The aim of this study was to compare post-operative C-reactive protein (CRP) between cases which underwent open appendectomy and laparoscopic appendectomy. Material and methods : This study was conducted on patients admitted for appendectomy in Imam Khomeini and Razi hospitals. Patients with perforated and gangrenous appendicitis, another pathological condition, renal failure, liver failure, history of taking drugs that interact with C-reactive protein (CRP), and pregnancy were excluded from this study. Cases were divided into children (5-15 years) and adults (16-65 years). Patients were randomly selected for open or laparoscopic appendectomy. SPSS version 16.0 (SPSS Inc, Chicago, IL, USA) was used for data analysis. T-test was used for comparison. Pearson and Spearman tests were used for correlation analysis. Results : There were no significant differences between CRP levels after laparoscopy in children vs. adult cases (p-value > 0.05, t-test). There was no significant difference between children and adults in pre-op CRP. There were significant differences between children and adults for 12 h and 24 h level of CRP after laparoscopic appendectomy (p < 0.05, t-test). Mean level of CRP in adults was significantly higher than children (p < 0.05, t-test). Level of CRP, 12 h after the procedure, was significantly higher in open appendectomy compared to laparoscopic surgery in adult cases (p = 0.09, t-test). In cases with body mass index (BMI) < 25 kg/m 2 , there was no significant difference between level of CRP before and after open or laparoscopic surgery. In cases with BMI ≥ 25 kg/m 2 , there was no significant difference between level of CRP of open and laparoscopic surgery (p > 0.05, t-test). Duration of surgery had no effect on level of CRP (p > 0.05, t-test). Conclusions : There was no significant difference between level of CRP after open and laparoscopic appendectomy, except in adult women. Level of CRP, 12 h and 24 h after surgery, was significantly higher in adult cases than children.